(untitled) (Research, Society and Development, 2020)
The aim of this study was to characterize the probiotic potential of 24 lactic acid bacteria (LAB) strains isolated from artisanal Coalho cheese from Pernambuco, Brazil by in vitro tests. The gastrointestinal tract (GIT) resistance, antimicrobial activity against intestinal pathogens, autoaggregation and coaggregation capacity, cell hydrophobicity, ß-galactosidase activity, deconjugate bile salt activity for the production of bile salt hydrolase (BSH), and the sensitivity to antibiotics were evaluated. Of the 24 strains, 22 remained viable to a simulated GIT. Two LAB inhibited the growth of Listeria monocytogenes and two inhibited Escherichia coli. The autoaggregation rate ranged from 27% to 96%, and the strains were able to coaggregate with Staphylococcus aureus and E. coli reaching levels between 58% and 47%, respectively. The hydrophobicity percentage ranged from 5% to 57%. Four strains were able to produce BSH. One LAB was able to produce up to 604 Miller units of ß-galactosidase. All strains were sensitive to five antibiotics and only two were resistant to vancomycin (30μg) and norfloxacin (10g). LAB strains which were able to overcome all barriers with a reduction of only one log cycle and LAB strains which were able to produce ß-galactosidase were identified by 16S rRNA sequence analysis as Lactococcus lactis subsp. Lactis, Enterococcus durans, and Enterococcus faecium. The evaluated LAB showed promising probiotic characteristics. Strains identified as L. lactis subsp. Lactis were selected for studies involving their technological potential to investigate the possible use of these microorganisms into a functional product.